(untitled) (Journal of the College of Basic Education, 2022)
The topic (Turkish writers and poets and their role in cultural diversity in Turkey) is of great importance as it sheds light on literature and poetry and its relation to politics. The research was divided into an introduction and four axes. The introduction talked about the roots of Turkish literature. The first axis involved the Turkish poet Nazim Hikmat, while the second one dealt with the Turkish woman represented by the novelist Khalida Adib. The third axis studied the life of the poet of Islam Mohammad Akef. The research was concluded with the fourth axis on the Turkish poet Tawfiq Fikret. The research reached a set of conclusions concerning the contemporary history of Turkey.